The impact of childhood acquired brain injury on siblings: a scoping review. (12th May 2023) - Vallee, Mélodie; Chevignard, Mathilde; Boissel, Anne
ABSTRACT: Objective: (a) To analyze the extent and nature of research on the impact of childhood acquired brain injury (ABI) on siblings, (b) to synthetize in a descriptive way the results of these studies and propose perspectives of care/support. Method: A literature search of 3 databases was performed up to August 2022. Studies addressing issues around siblings of children with ABI were included in the scoping review. Results: 25 articles were identified and analyzed. Results indicate that there is a paucity of research on this issue. However, interest in the subject has increased over past decades. Despite variable results, the current literature highlights the negative impact of ABI on family functioning and relationships. The trajectory and quality of life of siblings of children with ABI are modified. ABI causes intense and mixed emotions, psychological distress, behavioral difficulties and social stigma. Siblings have varied ways of coping with ABI and express particular needs that must be addressed. Conclusion: There is a significant impact of childhood ABI on siblings' subsequent life. Existing studies on this subject are few, heterogeneous, and sometimes contradictory. Further studies on this theme therefore appear necessary in order to propose appropriate support for patients' siblings according to their age and situation.